Treatment Patterns and Health Care Costs in Commercially Insured Patients with Follicular Lymphoma - Nathan H. Fowler; Guifang Chen; Stephen Lim; Stephanie Manson; Qiufei Ma; Frank Li (Journal of Health Economics and Outcomes Research)
**Background:** Few studies have estimated the real-world economic burden such as all-cause and follicular lymphoma-related costs and health care resource utilization (HCRU) in patients with follicular lymphoma (FL).